Service learning: implementation and evaluation in a information science curriculum - Mikelic, Nives; Tuđman, Miroslav; Matic, Sanja (2007)
We incorporated a first structured service learning program into our curriculum in Department of Information Science, Faculty of Philosophy, University of Zagreb. Goals and requirements for the service learning process were based upon our U.S. experience, established and approved in the beginning of the 2006/07 academic year. Various community non-profit organizations were identified as partners and developed into service learning sites. While in our Department students are prepared to become knowledgeable information scientists and school teachers who will provide quality education, this service learning program was implemented to help them become personally involved in providing their knowledge to users and school children and to do so with a caring professional attitude.
Sudjelovanje na kongresu s cjelovitim člankom i prezentacijom.
Projekt MZOS
Projekt MZOS
ENG